Farmers, institutions and technology in agricultural change processes: outcomes from Adaptive Research on rice production in Sulawesi, Indonesia. Issue 2 (2nd April 2016) - Flor, Rica Joy; Singleton, Grant; Casimero, Madonna; Abidin, Zainal; Razak, Nasruddin; Maat, Harro; Leeuwis, Cees
Abstract : International agricultural research centres use approaches which aim to create effective linkages between the practices of farmers, introduced technologies and the wider environment that affects farming. This paper argues that such new approaches require a different type of monitoring as a complement to conventional approaches that tend to favour a quantitative assessment of adoption and impact at the farm level. In this context, we examined monitoring data from an Adaptive Research (AR) project highlighting complementary qualitative analysis. Our emphasis is to capture the improvisational capacities of farmers and to reveal social and institutional constraints and opportunities in a broader innovation system. Our approach provided clear insights into how rice farmers adjusted their practices and how actors involved linked (or not) with others in the innovation system. We also demonstrated how institutions such as policies, religious rituals or service provider arrangements pose conditions that establish or constrain practices aligned with introduced technologies. A broader perspective in monitoring AR therefore provides important additional insights into the factors which shape outcomes in farming communities. To expand outcomes, AR projects should also pay attention to designing and testing new institutional arrangements that create enabling conditions for agricultural innovation.